Theoretical apparatus for analysis and synthesis of system communication protocol with a special set of services - Andonov, Antonio; Dimkin, Petar; Iliev, Filip (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Information about a project of total theoretical apparatus for analysis and synthesis of the pro-tocols for the control of selected system structures of communication system are described in the paper. The methods of analysis are oriented to essential proprieties of all referent model layers interfaces (capacity in both directions, elasticity for the whole set of services, code transparency, reliability, etc.) The methods of synthesis are oriented to the selection of optimality criteria, creation of hypothesis about protocol algorithm, hypotheses testing and to optimization of suitable protocol structures. After the elaboration of theoretical apparatus the solution moves to system application phase. In this step the theoretical apparatus is used for the implementation of typical solutions into the existing systems, for the elaboration of the recommendations for new standards creation and for the elaboration of the procedures for non-standard protocol creation. A lot of experience is laid in the introduced protocols. The consequence of individual stages is respected but expert approach without exact theoretical apparatus is presented.